2016
DOI: 10.4236/oje.2016.64015
|View full text |Cite
|
Sign up to set email alerts
|

Does <i>Typha</i> spp. Contribute to Wetland Waterloss and Health Risk: A Case Study of Hadejia Nguru Wetlands (HNW) System NE Nigeria

Abstract: The role of Typha spp. on water loss and public health has been uncertained and relatively poorly reported in Hadejia Nguru wetlands. This study investigated the extent to which Typha spp. contributed to evapotranspirative water loss and the level at which it provides suitable habitat for mosquito breeding. A comparative analysis between Typha swamp and open water was made to determine the evapotranspiration water loss and mosquito larva load accounted for by Typha swamp in the wetland. Maximum and minimum tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although generally edible, a few cases have implicated Typha in poisoning horses (Kingsbury 1964), cattle (Hurst 1942), and humans (Woodcock 1925). Large stands of Typha can harbor increased disease vectors, such as mosquitoes, snails and parasitic worms, potentially putting livestock and humans at greater disease risk (Cantrell 1981;Cogels et al 1997;Pfukenyi et al 2005;Pope et al 2005;Salako et al 2016). In the case of traditional grazing in Nigeria, large swaths of Typha have reduced the amount of available dryseason pasture (Degeorges and Reilly 2006).…”
Section: Agriculturementioning
confidence: 99%
“…Although generally edible, a few cases have implicated Typha in poisoning horses (Kingsbury 1964), cattle (Hurst 1942), and humans (Woodcock 1925). Large stands of Typha can harbor increased disease vectors, such as mosquitoes, snails and parasitic worms, potentially putting livestock and humans at greater disease risk (Cantrell 1981;Cogels et al 1997;Pfukenyi et al 2005;Pope et al 2005;Salako et al 2016). In the case of traditional grazing in Nigeria, large swaths of Typha have reduced the amount of available dryseason pasture (Degeorges and Reilly 2006).…”
Section: Agriculturementioning
confidence: 99%
“…In recent times, the emergence of invasive grass weeds has been identified as one of the factors affecting the Hadejia -Nguru wetlands. This had been reported in several studies, media and technical reports (Babagana et al, 2018;Abubakar S. Ringim et al, 2015;Salako et al, 2016). According to , most of the weeds are self-sown and they provide competition owing to their faster rate of growth in the initial stages, which reduce the crop yield by 50%.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, focused on how typha grass is militating against agricultural productivity along Hadejia River. Similar studies in the area are those of Zungum et al (2019) and Salako et al (2016). However, the latter studied the impact of typha grass on biodiversity loss in the wetlands, while the former carried out a research on how typha contributes to wetland water loss and health risk in the wetlands.…”
Section: Introductionmentioning
confidence: 88%
“…However, relationships between these invasive plants and mosquito larvae are inconsistent. Some research has found a positive relationship [ 90 , 91 ] and others show a negative [ 34 , 92 , 93 ] or non-significant relationship [ 40 , 41 , 94 , 95 ]. Management of vegetation in SCMs can be expensive and difficult to perform in a way that minimizes mosquito production [ 96 ].…”
Section: Discussionmentioning
confidence: 99%